POVERTY AS CHILD LABOR INTERNAL MIGRATIONâS DETERMINANT - Nurwita, Eva; Rinaldi, Rullan (Journal of Indonesian Economy and Business, 2009)
Migration is an unavoidable problem for economic development in third world countries. Indonesia is an archipelagic country with high viscosity population internalmigration. Over flooding wave of internal migration from periphery region to the core of growth poles increases the spatial disparities between regions. Not only for the labor force at their productive age, empirical evidences revealed the fact that the wave also involved children to work as child labor. This research tries to estimate how poverty in periphery determines the wave of migration toward urban agglomeration region at their core. Using data from the Indonesian Census 2000 for Java Island, global spatial effect and local statistics was estimated by spatial econometrics method.Keywords: Child Labor, Internal Migration, Spatial Econometrics, urban agglomeration